In vitro method for measuring synthesis rates in the intervertebral disc. - Bayliss, M; Urban, J; Johnstone, B; Holm, S (1986)
A method for culturing intervertebral disc tissue in vitro under conditions that control changes in hydration and minimize loss of proteoglycans has been developed. Disc slices were enclosed in small-pore dialysis tubing and incubated in medium containing polyethylene glycol (PEG). By varying the PEG concentration, different external swelling pressures could be applied to the tissue. The rate of glycosaminoglycan synthesis in rabbit and dog disc was then measured using [35S]sulphate as a precursor. Synthesis rates varied with final hydration of the tissue, and the highest rates were found at hydrations close to those found in vivo. Under conditions of controlled hydration, rabbit nucleus has a higher rate of glycosaminoglycan synthesis than annulus. However, the rates measured in sagittal slices of dog disc decreased from the outer to the inner regions of the anterior annulus, reaching a minimum value in the nucleus and then increasing again in the posterior part of the annulus. The results show that in the intervertebral disc, measured rates depend on culture conditions.